The Role of Social Media In The Formation of Gen Z Identity (Case Study at YP Unila High School, Bandar Lampung) - Yasmine Nabila Putri; Wawan Hernawan; Budhi Waskito (CONVERSE Journal Communication Science, 2026)
High exposure to diverse content on TikTok plays a significant role in shaping the identity of Generation Z students. Through continuous interaction with trends, challenges, and viral content, students are exposed to new values, norms, and communication styles that may influence how they perceive themselves and others. This process contributes to the formation of their mindset, interpersonal communication patterns, and ways of expressing emotions and opinions. As a result, TikTok becomes a social space where identity is constructed, negotiated, and displayed. However, this phenomenon also raises important concerns. The values and behaviors promoted on TikTok do not always align with the values instilled by family environments and educational institutions. Differences between online cultural trends and offline social norms may create tension in students’ identity development. They are often required to negotiate between expectations from their digital communities and the norms upheld by parents, teachers, and schools. Therefore, the main issue addressed in this study is how Generation Z students absorb, interpret, and adapt the influence of TikTok in the process of personal identity formation, and how this process interacts with family and school values. Using a qualitative approach, this research aims to examine the role of TikTok in shaping Generation Z’s identity in the context of interpersonal communication